Enhancing institutional quality to boost economic development in developing nations: New insights from CS-ARDL approach - Ijaz Uddin; Maaz Ahmad; Dilshod Ismailov; Muhammad Eid Balbaa; Akbarali Akhmedov; Sarvar Khasanov; Manzoor Ul Haq (Research in Globalization, 2023)
Institutional quality (IQ) plays a crucial role in achieving the Sustainable Development Goals. IQ is fundamental to SDG's 16, which promotes peaceful and inclusive societies, provides access to justice, and builds effective, accountable, and transparent institutions. Countries with strong institutions that uphold the rule of law, protect human rights, and combat corruption are more likely to achieve this goal and promote economic development. Therefore, this study examines the relationship between IQ and economic development, as measured by the human development index (HDI), in 70 developing countries between 2002 and 2018. To achieve the above mention objective, various econometric techniques were employed, including CIPS unit root, Westerlund (2007) co-integration, and Cross-sectional Augmented Autoregressive Distributed Lag, and robustness analysis conducted using Fully Modified Ordinary Least Square, Dynamic Ordinary Least Square, Augmented Mean Grouped, Impulse Response Function, and Variance Decomposition Analysis panel estimators. The study found that IQ and globalization have a positive, while inflation, unemployment, and corruption have a negative impact on HDI. The estimates from the Impulse Response Function show that IQ positively influences HDI from 2019 to 2028. Additionally, the Variance Decomposition Analysis reported that around 38% of the variations in HDI can be attributed to changes in IQ. To improve IQ, transparency must be prioritized as it is the foundation of IQ enhancement. Similarly, measures must be taken to combat corruption, and strong administrative intervention is required to advance economic development. These findings suggest that policymakers must prioritize improving institutional quality and fighting corruption to promote economic development in developing countries.
Keywords: 330; Developing countries; Economic development; Globalization; Institutional quality; Second-generation econometrics technique